2015
DOI: 10.1152/japplphysiol.01152.2014
|View full text |Cite
|
Sign up to set email alerts
|

Effect of unilateral nasal obstruction on tongue protrusion forces in growing rats

Abstract: Mouth breathing caused by nasal obstruction affects the normal growth and development of craniofacial structures, including changes in the orofacial muscles. Tongue muscles play an important role in patency of the pharyngeal airway, and changes in the breathing pattern may influence tongue function. The purpose of this study was to evaluate the effect of unilateral nasal obstruction during growth on contractile properties of the tongue-protruding muscles. Sixty 6-day-old male Wistar albino rats were divided ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
25
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 18 publications
(29 citation statements)
references
References 43 publications
4
25
0
Order By: Relevance
“…In previous studies, it has been reported that unilateral nasal obstruction before maturation of the respiratory function is well tolerated and affects the craniofacial complex (Otani-Saito et al, 2001), such as JOR (Funaki et al, 2014) and the contractile properties of the tongue-protruding muscles (Uchima Koecklin et al, 2015). Unilateral obstruction also induces atrophy of the ipsilateral olfactory bulb, associated with olfactory deprivation in rats (Meisami, 1976; Baekey et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…In previous studies, it has been reported that unilateral nasal obstruction before maturation of the respiratory function is well tolerated and affects the craniofacial complex (Otani-Saito et al, 2001), such as JOR (Funaki et al, 2014) and the contractile properties of the tongue-protruding muscles (Uchima Koecklin et al, 2015). Unilateral obstruction also induces atrophy of the ipsilateral olfactory bulb, associated with olfactory deprivation in rats (Meisami, 1976; Baekey et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…In our previous studies, we performed unilateral nasal obstruction in neonatal rat pups at 8 days of age, before the stabilization of SpO 2 levels (Funaki et al, 2014; Uchima Koecklin et al, 2015). The maturation of JOR was altered (Funaki et al, 2014) and the force of the tongue-protruding muscles increased (Uchima Koecklin et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations